Lessons learned?: Intended and unintended effects of India's second-generation maternal cash transfer scheme - Haaren, Paula von; Klonner, Stefan (Health economics, 2021)
The maternity benefit scheme piloted as Indira Gandhi Matritva Sahyog Yojana (IGMSY) since 2011 and recently rolled out as Pradhan Mantri Matru Vandana Yojana (PMMVY) incentivizes mothers to participate in infant health-promoting activities. It has become India's largest conditional cash transfer program ever, outrivaling the country's first-generation maternity benefit scheme Janani Suraksha Yojana (JSY), which incentivizes institutional delivery and has been criticized for its unintended side effects on fertility. We approach IGMSY's geographically targeted pilot phase as a natural experiment and use data from a large national health survey to estimate its effects by a matched-pair difference-in-differences approach. Consistent with the program's conditions, we find increases in infant immunization. As side effect, long-term utilization of public health facilities becomes more frequent and intervals between eligible births increase by 17%. Our findings suggest that India'ns second-generation maternity benefit scheme has been more carefully designed than its predecessor, with side effects that support the program's broader objectives. But both direct and indirect effects are small and can make only a small contribution to redressing India's dismal maternal and child health record.